Prevalence of severe acute malnutrition among 6-59 months children from community-based SAM management program in Dungarpur district of southern Rajasthan: diving deeper through study of block-wise prevalence - Suman, R. L.; Tomar, Madhusudan Singh; Agrawal, Kumaril; Dangi, Sushma; Yadav, Manju; Singh, Minakshi; Dutta, Vanita; Chauhan, Shiv Raj Singh; Rameshwar, Sheela; Chordia, Rajnish; Yadav, B. S. (International Journal of Contemporary Pediatrics, 2023)
Background: Acute malnutrition (severe and moderate) is a major public health problem in India and especially Rajasthan. National family health surveys now provide prevalence of SAM children till district level but there’s an undenying need for data at even more granular, like block level, to assess the field reality in more depth. The present study tries to demystify the same at block level by studying data collected from a community-based SAM management program i.e., AMMA (acute malnutrition management action) program in Dungarpur. Methods: As part of AMMA program, block wise data from 20 districts of Rajasthan was collected monthly during implementation and its dedicated MIS was used as the source of this data. The data includes information of all children screened in the age-group of 6-59 months in Dungarpur district which was subsequently analyzed and studied till block level. The SAM prevalence is assessed, using Mid Upper Arm Circumference (MUAC) of 6-59 months children. <12.5 cm of MUAC was considered as acute malnutrition while <11.5 cm of MUAC was considered as SAM as per WHO standards. Results: A total of 1,13,547 children were screened (84.91%) in the study period. A total of 4829 children (4.25%) were found with Acute Malnutrition, out of which 4622 were identified with moderately acute malnutrition (MAM) and 207 are identified with SAM. Out of total 207 children with SAM, 118 were girls (57%) while 89 (43%) were boys. The prevalence of SAM children in the district came out as 0.18% whereas state prevalence is 0.9%. Among blocks the SAM prevalence varied from as low as 0.02% in Dowda and Chikhali to as high as 0.63% in Jothari block. Conclusions: Prevalence of SAM in Dungarpur district is low at 0.18% but block-wise analysis helped in further disaggregating the burden. To identify all children with acute malnutrition in the district there’s an urgent need to do screening based on WFH Z-score instead of complete reliance on MUAC tape.